2012
DOI: 10.1016/j.apcatb.2011.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and bimetallic Rh and Pt NSR-catalysts prepared by controlled deposition of noble metals on support or storage component

Abstract: Mono- and bimetallic Rh and Pt based NO storage-reduction (NSR) catalysts, where the noble metals were deposited on the AlO support or BaCO storage component, have been prepared using a twin flame spray pyrolysis setup. The catalysts were characterized by nitrogen adsorption, CO chemisorption combined with diffuse reflectance infrared Fourier transform spectroscopy, X-ray diffraction, and scanning transmission electron microscopy combined with energy dispersive X-ray spectroscopy. The NSR performance of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…No effect is shown for propane because of the lack of activity at the test temperature of 200 °C. This inhibition impact is more pronounced with a high SO 2 dose. ,,,,,, Compared with HCs and NO, the negative impact of sulfur is less significant for CO in the practical application of DOCs.…”
Section: Impact Of So2 On Docsmentioning
confidence: 98%
“…No effect is shown for propane because of the lack of activity at the test temperature of 200 °C. This inhibition impact is more pronounced with a high SO 2 dose. ,,,,,, Compared with HCs and NO, the negative impact of sulfur is less significant for CO in the practical application of DOCs.…”
Section: Impact Of So2 On Docsmentioning
confidence: 98%
“…Typical catalyst formulations include different platinum group metals (PGM) such as Pt, Pd, or Rh, but the debate concerning the precise role of each constituent is still open. In particular, it has been reported that Pd or Rh are more reactive than Pt in the reduction of adsorbed NO x , more selective to N 2 , and with higher sulfur resistance [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…One of the main deactivation mechanisms of NSR catalysts is sulfur poisoning, 21 which reduces the performance of both the precious metal and the storage component. 17,[22][23][24] Oxides of sulfur (SO x ) exist in small but noticable quantities in fuel. Due to their higher affinity towards the storage and reduction components, SO x species compete with NO x for the same adsorption sites, binding much more strongly and blocking further NO x adsorption.…”
Section: Introductionmentioning
confidence: 99%